2000
DOI: 10.1128/jvi.74.10.4860-4867.2000
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid Organs as a Major Reservoir for Human T-Cell Leukemia Virus Type 1 in Experimentally Infected Squirrel Monkeys (Saimiri sciureus): Provirus Expression, Persistence, and Humoral and Cellular Immune Responses

Abstract: The aim of this study was to investigate the distribution of human T-cell leukemia virus type 1 (HTLV-1) in various organs of serially sacrificed squirrel monkeys (Saimiri sciureus) in order to localize the reservoir of the virus and to evaluate the relationship between viral expression and the humoral or cellular immune response during infection. Six squirrel monkeys infected with HTLV-1 were sacrificed 6, 12, and 35 days and 3, 6, and 26 months after inoculation, and 20 organs and tissues were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 36 publications
4
56
1
1
Order By: Relevance
“…Analyzing the HTLV-1 replication pattern over time in PBMCs and various organs from HTLV-1 experimentally infected monkeys revealed that PBMCs and lymphoid organs constitute the major reservoirs for HTLV-1. [50][51][52][53] A pattern of persistent clonal expansion of infected cells, identical to that observed in humans, was evidenced in the PBMCs of experimentally infected animals. 51 The dissemination of the virus throughout the different body compartments appeared to result from the cellular transport of the integrated provirus.…”
Section: Two-step Nature Of Htlv-1 Primary Infection In Vivomentioning
confidence: 59%
See 1 more Smart Citation
“…Analyzing the HTLV-1 replication pattern over time in PBMCs and various organs from HTLV-1 experimentally infected monkeys revealed that PBMCs and lymphoid organs constitute the major reservoirs for HTLV-1. [50][51][52][53] A pattern of persistent clonal expansion of infected cells, identical to that observed in humans, was evidenced in the PBMCs of experimentally infected animals. 51 The dissemination of the virus throughout the different body compartments appeared to result from the cellular transport of the integrated provirus.…”
Section: Two-step Nature Of Htlv-1 Primary Infection In Vivomentioning
confidence: 59%
“…After experimental infection of squirrel monkeys (Saimiri sciureus) with HTLV-1 infected cells, the virus appeared to be transcribed only transiently into the animal circulating blood, spleen and lymph nodes. 50 A stable disappearance of the viral expression occured at 2-3 weeks from inoculation, coinciding with the development of the anti-HTLV-1 immune response and the persistent detection of the provirus in PBMCs. Analyzing the HTLV-1 replication pattern over time in PBMCs and various organs from HTLV-1 experimentally infected monkeys revealed that PBMCs and lymphoid organs constitute the major reservoirs for HTLV-1.…”
Section: Two-step Nature Of Htlv-1 Primary Infection In Vivomentioning
confidence: 99%
“…Monkeys and rabbits have been 4 used to examine HTLV-1 infection, replication, disease manifestations, immune response, and vaccine development [15][16][17][18][19][20]. However, rats and mice are more attractive models for HTLV-1 study because of the ease with which they can be genetically manipulated.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, peripheral blood mononuclear cells were the main infected cell compartment, but other HTLV-1-infected tissues including salivary and thyroid glands, lung, liver, pancreas, intestine, muscle and spinal cord were sporadically detected in individual monkeys (Kazanji et al, 2000).…”
Section: Animal Models: a Broad In Vivo Tropismmentioning
confidence: 99%
“…HTLV-1 infection and spreading has also been closely examined after intravenous inoculation of adult squirrel monkeys (Saimiri sciureus) (Kazanji et al, 1997(Kazanji et al, , 2000Mortreux et al, 2001). In this model, peripheral blood mononuclear cells were the main infected cell compartment, but other HTLV-1-infected tissues including salivary and thyroid glands, lung, liver, pancreas, intestine, muscle and spinal cord were sporadically detected in individual monkeys (Kazanji et al, 2000).…”
Section: Animal Models: a Broad In Vivo Tropismmentioning
confidence: 99%